2019
DOI: 10.1002/acm2.12623
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of distal esophageal carcinoma plans for patients treated with small‐spot intensity‐modulated proton versus volumetric‐modulated arc therapies

Abstract: Background Esophageal carcinoma is the eighth most common cancer in the world. Volumetric‐modulated arc therapy (VMAT) is widely used to treat distal esophageal carcinoma due to high conformality to the target and good sparing of organs at risk (OAR). It is not clear if small‐spot intensity‐modulated proton therapy (IMPT) demonstrates a dosimetric advantage over VMAT. In this study, we compared dosimetric performance of VMAT and small‐spot IMPT for distal esophageal carcinoma in terms of plan quality, plan rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 58 publications
1
61
0
Order By: Relevance
“…The use of proton beam therapy (PBT) in the radiooncological treatment of oesophagal carcinomas is the result of efforts to reduce the known toxicities further. Previously published dosimetric comparisons of PBT and IMRT indicate a considerable reduction of radiation exposure of organs at risk, especially regarding heart and lungs [23][24][25]. Welsh [26], in a dosimetric study, investigated the role of intensity-modulated proton therapy (IMPT) for advanced distal oesophagal tumors and showed a considerable reduction of the dose to the organs at risk compared to IMRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of proton beam therapy (PBT) in the radiooncological treatment of oesophagal carcinomas is the result of efforts to reduce the known toxicities further. Previously published dosimetric comparisons of PBT and IMRT indicate a considerable reduction of radiation exposure of organs at risk, especially regarding heart and lungs [23][24][25]. Welsh [26], in a dosimetric study, investigated the role of intensity-modulated proton therapy (IMPT) for advanced distal oesophagal tumors and showed a considerable reduction of the dose to the organs at risk compared to IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Shiraishi [27] demonstrated a significant decrease in radiation exposure to the whole heart and to the cardiac structures comparing PBT vs IMRT. Liu [25] compared at planning level the potential of VMAT versus IMPT for distal oesophagal cancer patients. The study concluded that protons resulted in dosimetrically preferable plans compared to VMAT.…”
Section: Introductionmentioning
confidence: 99%
“…58 Liu et al carried out a comparative study between small-spot IMPT and volumetric-modulated arc therapy (VMAT), and found that small-spot IMPT significantly improved sparing of heart, liver, and lungs with clinically acceptable plan robustness. 34 Most recently, Lin et al reported the result of a phase IIB trial that for locally advanced esophageal cancer, proton beam therapy (PBT) reduced the risk and severity of adverse events (AEs) while maintaining similar progression-free survival (PFS) when compared with IMRT. 59 Specifically for IMPT, different configurations may lead to different outcomes, such as spot sizing and spacing.…”
mentioning
confidence: 99%
“…There now exists a significant body of in silico and in vivo literature describing the potential to decrease integral RT dose exposure to normal tissues when PBT is used across several body sites. [33][34][35][36][37][38][39][40][41] For breast cancer specifically, small series have described significantly reduced cardiac and pulmonary exposures when RT is delivered with photons compared with protons, with particular emphasis on cardiac structures. [20][21][22]42 However, clinicians and national clinical trial protocols 43 continue to base RT planning goals (and, by extrapolation, plan quality) on historical photon constraints.…”
Section: Discussionmentioning
confidence: 99%